Efeito da suplementação com açaí Juçara sobre o número de focos de criptas aberrantes e expressão de SOD1 em ratos submetidos à carcinogênese colorretal - Reis, Schalana Oliveira dos (2016)
Colorectal Cancer (CC) is one of the most frequent cancers in the world and one of the most important causes of death in Brazil. It is the third most common cancer in men and second in women worldwide. The surface of the large intestine is coated by Lieberkuhn crypts, invaginated absorptive cells. CC is initiated by appearance of Aberrant Crypt Foci (ACF) and morphological changes in the crypts of Lieberkuhn. Studies have shown that antioxidants in fruits and vegetables can contribute to the prevention of some diseases, like cancer. This preventive action is considered direct when antioxidant acts on elimination of reactive species and indirect when improves expression or activity of endogenous antioxidant enzymes such as SOD1. The Juçara acai has been highlighted by its rich composition of antioxidants, very important in the neutralization of reactive species. In order to asses the Juçara intake related to the number of ACF and SOD1 expression in CC, a study was conducted on 16 samples of large intestine of rats with carcinogenesis with 1,2- dimethylhydrazine (DMH). It was measured the amount of ACF area and the expression of SOD1 score rats supplemented and non supplemented with Juçara. The supplementation with acai juice Juçara promoted fewer aberrant crypt foci in the colon mucosa of rats induced to carcinogenesis. Superoxide dismutase 1 was expressed in colorectal mucosa of rats induced or not to carcinogenesis. Supplementation with Juçara acai juice resulted in greater expression and SOD1 occupancy percentage in the large intestine. Thus, acai Juçara can be an ally in colorectal cancer prevention, since the reduction in number of lesions in colon epithelium and can aid in stimulating the production of antioxidant enzymes. These results open perspectives for the use of acai Juçara in dietary supplementation, development of products and drugs that promote the prevention and treatment of colorectal cancer.